(untitled) (JURNAL ENFIT : Entomologi dan Fitopatologi, 2023)
One of the diseases that often affects the production rate of cabbage is clubroot disease caused by the fungus Plasmodiophora brassicae Wor. This study aims to determine the effect of the application of Trichoderma sp. and PGPR in controlling clubroot disease in cabbage. The research was carried out from August to November at the Laboratory of Biological Agency for the Protection of Food Crops and Horticulture in Kalasey and in Kakaskasen Village, North Tomohon District, Tomohon City. The study was conducted using a randomized block design (RAK) with 4 treatments and 4 replications, namely Treatment A = Trichoderma sp. (250ml/plant), Treatment B = PGPR (250ml/plant), Treatment C = Trichoderma sp. and PGPR (250ml+250 ml/plant), Treatment K = Control. Based on the results of observations of clubroot disease symptoms on cabbage plants, above the ground the leaves appear pale green to yellowish and wilted during the day and look fresh again in the afternoon. In further attacks the affected cabbage plants become stunted. Typical symptoms of this disease can be seen in the swollen roots of the plant. The results showed that the application of Trichoderma sp. and PGPR effect in controlling clubroot disease in cabbage plants. Where the best treatment in suppressing clubroot disease is the treatment of Trichoderma sp. and PGPR with the lowest percentage of 6.25%, followed by Trichoderma sp. with the lowest percentage of 7.50% and PGPR treatment with the lowest percentage of 12.50%. The average wet weight per plant crop showed the highest yield, namely in the treatment of Trichoderma sp. and PGPR 1090.5 gr and the lowest yield was in the Control treatment 860 gr.